Comprehensive genomic characterization and expression analysis of calreticulin gene family in tomato - Muhammad, Tayeb; Yang, Tao; Wang, Baike; Yang, Haitao; Tuerdiyusufu, Diliaremu; Wang, Juan; Yu, Qinghui (Frontiers in Plant Science, 2024)
Calreticulin (CRT) is a calcium-binding endoplasmic reticulum (ER) protein that has been identified for multiple cellular processes, including protein folding, regulation of gene expression, calcium (Ca 2+ ) storage and signaling, regeneration, and stress responses. However, the lack of information about this protein family in tomato species highlights the importance of functional characterization. In the current study, 21 CRTs were identified in four tomato species using the most recent genomic data and performed comprehensive bioinformatics and SlCRT expression in various tissues and treatments. In the bioinformatics analysis, we described the physiochemical properties, phylogeny, subcellular positions, chromosomal location, promoter analysis, gene structure, motif distribution, protein structure and protein interaction. The phylogenetic analysis classified the CRTs into three groups, consensus with the gene architecture and conserved motif analyses. Protein structure analysis revealed that the calreticulin domain is highly conserved among different tomato species and phylogenetic groups. The cis-acting elements and protein interaction analysis indicate that CRTs are involved in various developmental and stress response mechanisms. The cultivated and wild tomato species exhibited similar gene mapping on chromosomes, and synteny analysis proposed that segmental duplication plays an important role in the evolution of the CRTs family with negative selection pressure. RNA-seq data analysis showed that SlCRTs were differentially expressed in different tissues, signifying the role of calreticulin genes in tomato growth and development. qRT-PCR expression profiling showed that all SlCRTs except SlCRT5 were upregulated under PEG (polyethylene glycol) induced drought stress and abscisic acid (ABA) treatment and SlCRT2 and SlCRT3 were upregulated under salt stress.Overall, the results of the study provide information for further investigation of the functional characterization of the CRT genes in tomato.